Bimodal stimulation in children with inner ear malformation: One side cochlear implant and contralateral auditory brainstem implant. (22nd January 2020) - Batuk, Merve Ozbal; Cinar, Betul Cicek; Yarali, Mehmet; Aslan, Filiz; Ozkan, Hilal Burcu; Sennaroglu, Gonca; Yucel, Esra; Bajin, Munir Demir; Bilginer, Burcak; Sennaroglu, Levent
Abstract: Objective: To determine audiological outcomes of children who use a cochlear implant (CI) in one ear and an auditory brainstem implant (ABI) in the contralateral ear. Design: Retrospective case review. Setting: Tertiary referral hospital. Participants: Twelve children followed with CI and contralateral auditory brainstem implant (ABI) by Hacettepe University Department of Otorhinolaryngology and Audiology in Turkey. All children were diagnosed with different inner ear malformations with cochlear nerve aplasia/hypoplasia. CI was planned in the ear with better sound detection during behavioural testing with inserted ear phones and with better CN as seen on MRI. Due to the limited auditory and speech progress with the cochlear implant, ABI was performed on the contralateral ear in all subjects. Main outcome measures: Audiological performance and auditory perception skills of children with cochlear nerve deficiency (CND) who use bimodal electrical stimulation with CI and contralateral ABI. Results: Mean age of the subjects was 84.00 ± 33.94 months. Age at CI surgery and ABI surgery was 25.00 ± 10.98 months and 41.50 ± 16.14 months, respectively. However, hearing thresholds only with CI and only with ABI did not reveal significant difference, and auditory perception scores improved with bimodal stimulation. The MAIS scores were significantly improved from unilateral CI to bimodal stimulation ( P  = .002). Pattern perception and word recognition scores were significantly higher with the bimodal condition when compared to CI only and ABI only conditions. Conclusion: Children with CND showed better performance with CI and contralateral ABI combined. Depending on the audiological and radiological results, bimodal stimulation should be advised for children with CND.